ANALISIS RASIO PROFITABILITAS (NPM, ROA) DAN RASIO LIKUIDITAS (CR, QR) DALAM MENILAI KINERJA KEUANGAN TERHADAP PT ASTRA INTERNATIONAL TBK PERIODE 2018-2022 - Submission JORAPI; Rio Aprilian; Gatut Dradjad Purwoko (Journal of Research and Publication Innovation, 2024)
The purpose of this study is a type of quantitative research with the aim of knowing the financial performance of PT. Astra Internasional TBK Period 2018- 2022 based on liquidity ratios and profitability ratios. The sample is taken from the company's financial statements PT. Astra International TBK. The type of data used in this study is secondary data obtained from the company's annual financial statements. Data collection was carried out using documentation techniques, namely recording the required data from the Indonesian Stock Exchange website. In this study, the data source used was secondary data collection. Based on the results of research data using the calculation of liquidity ratios and profitability ratios regarding the financial performance of PT. Astra International TBK 2018-2022, the authors conclude that financial performance in terms of liquidity ratios, seen from the calculation of the current ratio and quick ratio is still not optimal because the value is still below the industry average standard. This means that the company has not been optimal in managing its working capital. And financial performance in terms of profitability ratios, seen from the calculation of GPM, NPM, ROA and ROE also the number of ratios obtained is still below the average standard ratio. Overall condition of the company in terms of profitability ratios can be said to be less than optimal. The company's management has not been maximal in managing liabilities and maximizing the use of its current assets. Keywords: Liquidity Ratio, Profitability Ratio, Financial Performance.